Clinical characteristics of children with MIS-C fulfilling classification criteria for macrophage activation syndrome - Buda, Piotr; Strauss, Ewa; Januszkiewicz-Lewandowska, Danuta; Czerwinska, Ewa; Ludwikowska, Kamila; Szenborn, Leszek; Gowin, Ewelina; Okarska-Napierała, Magdalena; Kuchar, Ernest; Ksia̧zyk, Janusz (Frontiers in Pediatrics, 2022)
Background Macrophage activation syndrome (MAS) is a potentially life-threatening complication of various inflammatory disorders, including multisystem inflammatory syndrome in children (MIS-C). MIS-C refractory to treatment should raise suspicion of MAS, which can be fatal if a definitive diagnosis is delayed. Unfortunately, there is a lack of data on MAS in children with MIS-C. Objective Our study aims to analyze the risk factors for the development of MAS in MIS-C, its clinical course and response to treatment, and identify predictive factors for pediatric intensive care. Material and methods We analyzed data from the Polish MIS-C registry of the MultiOrgan Inflammatory Syndromes COVID-19 Related Study. Patients were diagnosed according to the WHO MIS-C definition and treated according to national guidelines (Polish Pediatric Society) based on international consensus. MAS definition was based on 2016 Classification Criteria for Macrophage Activation Syndrome Complicating Systemic Juvenile Idiopathic Arthritis. Results Two-hundred and seventy four children met the study inclusion criteria. Fifty-nine patients fulfilled MAS classification criteria, nine of which required admission to the pediatric intensive care unit (PICU). MIS-C patients with MAS were significantly older than patients without MAS (median 11.2 vs. 8.1 years). Multivariable analysis showed that age, symptoms characteristic of atypical Kawasaki disease, and skin erosions were significant factors associated with MAS in MIS-C patients. Analysis of laboratory parameters showed that on admission, MIS-C patients with MAS had significantly lower median lymphocyte and platelet counts, albumin and sodium levels, and higher median levels of C-reactive protein, procalcitonin, ferritin, D-dimers, triglycerides, serum creatinine, urea, and γ-glutamyl transpeptidase, and neutrophil count. Multivariate analysis showed that higher procalcitonin, ferritin, and fibrinogen levels at admission were predictive of MAS. Only elevated troponin level was a factor indicating a requirement of PICU hospitalization for children with MAS. MIS-C patients fulfilling MAS criteria were treated more often with intravenous immunoglobulins and steroids than children without MAS. Children with MAS more often required mechanical ventilation. None of the patients required biological agents. Conclusions The clinical course of MAS in MIS-C seems milder, treatment less aggressive, and the prognosis better than expected based on the current knowledge on MAS complicating other rheumatological diseases.